Evaluasi Sistem Informasi Manajemen Digital melalui Sosialisasi Masyarakat (Studi kasus Desa Sumberlele Kabupaten Probolinggo) - Supriyanto, Supriyanto; Rahmadi, Andhi Nur; Sucahyo, Imam; Mubaroq, Alvan (Universitas Pahlawan Tuanku Tambusai, 2025)
One of the factors that causes the digital gap between urban and rural areas is the unequal distribution of infrastructure and availability of human resources and digital technology which influences the use of Digital Management Information systems at the village level, precisely in the form of web bases or dashboards that have been integrated in the form of Apps. Sumberlele Village is a village in Kraksaan District, Probolinggo Regency, East Java Province, Indonesia, where the village government area has made progress towards one of them having a more very influential role, namely the role of digital transformation, in an effort to create a system. Village Service Management Information. This service also aims to provide a more complex understanding and explanation to the community about how to implement a digital information system through evaluation of digital management information systems through community socialization of sumberlele village, kraksaan district. This digital form is very important and helps to facilitate village bureaucratic services to provide good service to village communities when applying administration, daily village office administrative interactions.